Macroeconomic policy and poverty in Brazil - Edward Amadeo; Marcelo Cortes Neri (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1997)
This paper discusses the structural and macroeconomic determinants of poverty in the recent Brazilian experience. The paper looks at the evolution of the main structural determinants of poverty in Brazil during the last two decades. It decomposed. changes of various poverty indexes across different groups assigned by characteristics of the heads of households (i.e.; gender, years, schooling, race, working class, sectors of activity, region, population density). Next this decomposition is taken one step further by disentangling changes in these different poverty cells in terms of their respective changes in mean and in the degree of inequality of per capita income. The main lesson here is that inequality reduction is a fundamental component of poverty alleviation policies. Another part of the paper describes the evolution of poverty, inequality and macroeconomic developments in Brazil during the last decade and develops an aggregate monthly time series analysis of the determinants of poverty in the 1980-96 period. This analysis showed that higher inflation and higher unemployment imply lower per capita earnings for all deciles. The direct effects of inflation on per capita family earnings were somewhat milder and decreases as we move to the upper tail of the distribution. In other words, poverty tend to be more adversely affected by higher inflation rates than mean incomes. Similarly, the unemployment elasticity of per capita earnings decreases as we move towards the upper tail of the distribution.
Keywords: 330